2009
DOI: 10.1007/s12011-009-8491-x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Increase in the Mammillary Bodies with Aging

Abstract: To elucidate compositional changes of the mammillary body with aging, the authors investigated age-related changes of elements, relationships among their elements, and gender differences in the mammillary bodies by direct chemical analysis. After ordinary dissection at Nara Medical University was finished, the mammillary bodies were resected from the cerebra of the subjects. The subjects consisted of 19 men and 25 women, ranging in age from 70 to 101 years (average age = 83.8 +/- 7.2 years). After ashing of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
9
1
Order By: Relevance
“…Therefore, the authors examined in detail the differences in the average contents of P, Zn, and Na between the gray and white matters, including the anterior commissure, corpus callosum, mammillary body, olfactory bulb and tract, and pineal body analyzed previously by us. The average contents of P were 5.14± 0.97 mg/g in the fornix, 7.67±1.33 mg/g in the corpus callosum (trunk) [1], and 5.51± 1.04 mg/g in the anterior commissure [2] of the white matter and 3.33±1.09 mg/g in the hippocampus, 2.67±0.87 mg/g in the dentate gyrus, 3.20±0.86 mg/g in the mammillary body [5], 2.11±0.79 mg/g in the olfactory bulb and tract [4], and 28.79±32.88 mg/g in the pineal body [3]. Namely, the average content of P was higher than 5.1 mg/g in all of three white matters, whereas the average content of P was less than 3.3 mg/g in all of four gray matters except for the pineal body.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the authors examined in detail the differences in the average contents of P, Zn, and Na between the gray and white matters, including the anterior commissure, corpus callosum, mammillary body, olfactory bulb and tract, and pineal body analyzed previously by us. The average contents of P were 5.14± 0.97 mg/g in the fornix, 7.67±1.33 mg/g in the corpus callosum (trunk) [1], and 5.51± 1.04 mg/g in the anterior commissure [2] of the white matter and 3.33±1.09 mg/g in the hippocampus, 2.67±0.87 mg/g in the dentate gyrus, 3.20±0.86 mg/g in the mammillary body [5], 2.11±0.79 mg/g in the olfactory bulb and tract [4], and 28.79±32.88 mg/g in the pineal body [3]. Namely, the average content of P was higher than 5.1 mg/g in all of three white matters, whereas the average content of P was less than 3.3 mg/g in all of four gray matters except for the pineal body.…”
Section: Discussionmentioning
confidence: 99%
“…The authors previously investigated age-related changes of elements in the corpora callosa [1] and anterior commissures [2] of the white matter and the pineal bodies [3], olfactory bulbs and tracts [4], and mammillary bodies [5] of the gray matter. It was found that a very high accumulation of Ca and P occurred in the pineal body at old age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To elucidate compositional changes of the brain with aging, the authors previously investigated age-related changes of elements in the corpus callosum [1] and anterior commissure [2] of the white matter and in the pineal body [3], olfactory bulb and tract [4], and mammillary body [5] of the gray matter.…”
Section: Introductionmentioning
confidence: 99%